Stalin on Linguistics and Other Essays - Gray, P. author. aut Link
XIV, 267 p.
Keywords: Piers Gray was one of the most brilliant literary writers of his generation. These essays ranging from Oscar Wilde to Levin, from Shakespeare to pulp fiction, use the full resources of literary and linguistic analysis to produce a reading of European culture and society in the twentieth century. In his final posthumous essay On Linearity , Gray summons all his reading and knowledge to deliver his final judgement on life and death.